KEWENANGAN BADAN PENGELOLAAN LINGKUNGAN HIDUP DALAM MELAKUKAN MEDIASI KASUS LINGKUNGAN (Studi kasus pada BPLH Kota Tarakan) - Ratna, Wiwin Dwi (JURNAL AKTA YUDISIA, 2016)
Abstract Amendments to the laws on local government undnagan impact on local government authority in running the affairs of government. For 10 years Indonesian running the regional autonomy system using Law No. 32 of 2004 on local government, and amendments thereto, for the moment the law declared invalid by the enactment of Law No. 23 Year 2014 on Regional Government, the State Gazette of the Republic of Indonesia Year 2014 No. 244, on October 2, 2014. in the Act governing the affairs of government that must be done by the central government, provincial government and local government district / city. Some affairs are regulated in more detail in the Government Regulation No. 18 Year 2016 concerning the Region, which regulates the scope of authority in dealing with government affairs. PP No. 1/2016 outlining the areas that must be held in an area with indicator, scale of values that can be found local work load. Environmental Management itself in Law number 23/2014 and Government Regulation No. 1/2016 is a category / classified in the Mandatory government affairs unrelated to basic services.Keywords: Local authorities, Environment, government affairs